Impact of Project-Based Learning (PBL) Integrated with Google Classroom on Improving English Writing Skills in a Bangladeshi University - Karim, Mohammad Rejaul; Na, Kew Si (International Journal of Learning, Teaching and Educational Research, 2024)
Developing tertiary students’ writing skills is a crucial issue. Teachers integrate writing projects with Google Classroom to develop students’ writing skills, although the impact of this learning model has not yet been determined in the Bangladeshi higher education context. This research explored the impact of project-based learning (PBL), supported by Google Classroom, on developing the writing skills of tertiary students in Bangladesh. This quasi-experimental study analyzed essays written by 30 control- and 30 experimental-group students. Additionally, in-depth interviews were conducted with 10 students to collect data. A t test and thematic analysis were conducted for quantitative and qualitative data analysis, respectively. This quasi-experimental research used a pre-test/post-test and control group design. The experiment was implemented for the experimental group using PBL with Google Classroom and for the control group using the conventional teaching method. The pre-test results indicate no differences between the groups (t = 0.55, p > 0.05) in terms of writing proficiency before the intervention. Nevertheless, the post-test yielded a t value of 3.43 (p < 0.01), which was statistically significant in favor of the experimental group. This suggests the enhancement of students’ writing skills through PBL with Google Classroom. These results demonstrate the benefits of the combination of interactive activities and social interaction conducive to writing tasks provided by this blended learning strategy. The implications are that teachers can blend PBL with Google Classroom for more active learning environments that align with students with real-world writing tasks. Limitations involved a small sample size and study duration. Future work should target larger, more diverse samples and incorporate qualitative work to deepen understanding of the learning process and outcomes. https://doi.org/10.26803/ijlter.23.9.6